2019 8th International Workshop on Tracking, Telemetry and Command Systems for Space Applications (TTC) 2019
DOI: 10.1109/ttc.2019.8895426
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis and Implementation of Effective Receivers for Telecommand Space Links

Abstract: This paper deals with the feasibility of the new receiver scheme for telecommand space links, based on the adoption of short low-density parity-check codes recently introduced in the standard. Being able to reduce significantly the required signal-to-noise ratio, these codes have an impact on the acquisition, tracking and synchronization issues. All these aspects have been faced, both theoretically and practically through the realization of a breadboard that implements the core elements of the on-board receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…A Field-Programmable Gate Array (FPGA) implementation of the in-space TC receiver, working in real time, was presented in [9,10]. In contrast, in this paper we address the ground segment transmission chain.…”
Section: On-ground Telecommand Synchronization and Channel Coding Sub...mentioning
confidence: 99%
See 3 more Smart Citations
“…A Field-Programmable Gate Array (FPGA) implementation of the in-space TC receiver, working in real time, was presented in [9,10]. In contrast, in this paper we address the ground segment transmission chain.…”
Section: On-ground Telecommand Synchronization and Channel Coding Sub...mentioning
confidence: 99%
“…The reason why LDPC codes need longer start sequences is that, thanks to their coding gain, they are able to work at lower SNR. Then, a longer sequence is used to reliably acquire CLTU synchronization [9,10]. The CLTU generation block may also append a tail sequence for some configurations:…”
Section: Cltu Generationmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the development of the baseband receiver, we presented a preliminary work in [11], which focused on the frame synchronization module. Indeed, the authors of [12] have identified the frame synchronization process as one of the most critical aspects of the receiving chain, which creates a bottleneck. In Earth observation missions, the amount of collected data to be delivered to ground stations has reached several terabytes per day [13].…”
Section: Introductionmentioning
confidence: 99%